2013
DOI: 10.4103/0975-9476.113880
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antihyperlipidemic activity of hydroalcoholic extract of Withania coagulans Dunal dried fruit in experimental rat models

Abstract: Objective:Evaluation of antidiabetic potential of the hydroalcoholic extract of Withania coagulans Dunal dried fruit (WCDF) alone and in combination with glipizide, in streptozotocin-induced diabetes, and evaluation of possible antihyperlipidemic activity of the same extract in high-cholesterol diet-induced hyperlipidemia, in albino rats.Materials and Methods:Experimental diabetes was induced in 30 albino rats with intraperitoneal injection of streptozotocin (55 mg/kg). The rats were divided into five groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The serum collected on 21st day of the treatment period was also analyzed for total cholesterol (TC), high density lipoprotein cholesterol (HDLc) and triglyceride (TG) levels by using diagnostic kits. The low density lipoprotein cholesterol (LDLc) and very low density lipoprotein-cholesterol (VLDLc) were also calculated by using Friedwald's formula [2] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum collected on 21st day of the treatment period was also analyzed for total cholesterol (TC), high density lipoprotein cholesterol (HDLc) and triglyceride (TG) levels by using diagnostic kits. The low density lipoprotein cholesterol (LDLc) and very low density lipoprotein-cholesterol (VLDLc) were also calculated by using Friedwald's formula [2] .…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus and its associated acute and long-term complications are an important health hazard globally. Its prevalence has now reached pandemic proportions in India [2] . It is reported that the four countries namely China, India, Indonesia and Japan from Asia are center for the global epidemic of diabetes and the number of diabetic patients worldwide has doubled in the past two decades [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyay and et al reported antihyperglycemic effect of WCE in diabetic patients (1). Another study revealed anti-hyperlipidemia effects of WCE in rats (6). It has been reported that Withaferin A has protective effects against Alzheimer's disease (7).…”
Section: Introductionmentioning
confidence: 98%
“…Due to this reason, the need for novel treatment strategies which offer more benefits to patients suffering from T2DM was created, focusing on treatments that produce better glycemic control, appetite regulation, blood pressure, lipid reduction and weight loss. Also, there has been a growing emphasis on therapy of hyperlipidemia associated with diabetes to develop newer antidiabetic agents with potential anti-hyperlipidemic effects [4] .…”
Section: Introductionmentioning
confidence: 99%